Proceedings of the 2nd Padang International Conference on Education, Economics, Business and Accounting (PICEEBA-2 2018) 2019
DOI: 10.2991/piceeba2-18.2019.114
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ Worksheet Based on Higher Order Thinking Skills for Economics Learning in Senior High School

Abstract: Higher order thinking skills test is formulated for improving student critical thinking abilities. This study is conducted by using research and development approach. The aim of this study is to develop student worksheet based on higher order thinking skills for economics learning in senior high school and will be carried out for 2 years. This study uses the Plomp (1982) model. The development procedures of the Plomp model consists of five steps, namely; (1) initial investigation, (2) design, (3) construction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
2
Order By: Relevance
“…questions. Such questions require students to use higher order thinking skills and hence call for Economics teachers to design learning strategies that can encourage such skills (Kurniawati, 2021). Romadhoni and Nurlaela (2018) state that higher order questions are the questions that require students to conclude, hypothesise, analyse, apply, synthesise, evaluate, and engage in comparing and contrasting the ideas they come across.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…questions. Such questions require students to use higher order thinking skills and hence call for Economics teachers to design learning strategies that can encourage such skills (Kurniawati, 2021). Romadhoni and Nurlaela (2018) state that higher order questions are the questions that require students to conclude, hypothesise, analyse, apply, synthesise, evaluate, and engage in comparing and contrasting the ideas they come across.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is against this background that a problem statement was formulated which states that an over-reliance on teaching methods that do not actively engage http://ijlter.org/index.php/ijlter students in the learning process is a contributing factor to inadequate development of Economics students' higher order thinking skills, resulting in student under-achievement in the higher-order questions. The challenge that Economics students have in demonstrating higher-order thinking skills is highlighted in the study by Kurniawati (2021), which found that higher order thinking skills are still low among Economics students. The results of that study indicated that most of the students who took the test that consisted of lower and higher order questions did better in lower order questions; only a few performed well in higher order questions (Kurniawati, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berhasil tidaknya proses pembelajaran juga sangat dipengaruhi oleh lingkungan belajar (Kurniawati, Tasman, & Siwi, 2019).…”
Section: Peran Pendidikan Kewirausahaan Dan Self Efficacy Terhadap Intensi Berwirausaha Mahasiswaunclassified
“…Selain (OJS) berdampak pada karya ilmiah yang dihasilkan, kegiatan membaca semacam ini akan membuat materi pembelajaran guru di dalam kelas lebih kekinian dan tidak lagi itu ke itu saja dari semester ke semester. Hal ini sejalan dengan pendapat Kurniawati, Tasman, & Siwi, M. K. (2019) bahwa guru hendaklah memiliki kemampuan untuk mengembangkan materi ajar, memilih metode pembelajaran yang tepat termasuk penggunaan media pembelajaran yang sesuai. Kedua, kegiatan penelitian dan penulisan karya ilmiah biasanya dilakukan secara kolaboratif.…”
Section: Pendahuluanunclassified